Communicating the health value of extra-virgin olive oil: an investigation of consumers' responses to health claims. Issue 2 (17th September 2020) - Pichierri, Marco; Peluso, Alessandro M.; Pino, Giovanni; Guido, Gianluigi
Abstract : Purpose: This research investigates the effectiveness of the four health claims that the European Union (EU) authorized for extra-virgin olive oil (EVOO) in terms of perceived text clarity, text interestingness, message credibility and information diagnosticity, along with the claims' effect on product attractiveness and consumers' purchase intention. Design/methodology/approach: An experimental study with 185 participants investigated consumer response to the four claims. A one-way MANOVA analyzed differences in the aforementioned variables, while a sequential mediation model assessed the relationship among perceived text clarity of the EVOO health claims, information diagnosticity, product attractiveness and purchase intention. Findings: The four EU-authorized health claims differ in terms of perceived text clarity, message credibility, information diagnosticity and product attractiveness. Specifically, the health claim on EVOO polyphenols scored lower than the other three health claims on the aforementioned dependent variables. Importantly, clearer health claims are perceived as more useful and may increase product attractiveness and consumers' purchase intention. Originality/value: The research sheds light on the effectiveness of EVOO health claims. Since the use of such health claims is not a common practice in the EVOO market, a deeper understanding of consumers' perception and attitude toward them could inspire better guidelines and suggestions for claim usage and improvement.